Human eyelid behavior is driven by segmental neural control of the orbicularis oculi - Jinyoung Kim; Ashley Shirriff; Jordan N. Cornwell; Maria Paula Quintero Mutis; Ereni Delis; Sophia Wang; Daniel B. Rootman; Tyler R. Clites (Proceedings of the National Academy of Sciences, 2025)
The eyelid performs critical functions to protect the eye and preserve functional vision. These functions are driven by contraction of the orbicularis oculi (OO), which is a unique skeletal muscle with a circular geometry and diffuse innervation. It is thought that this distributed innervation may allow for differential segmental activation and contraction, but it is not currently understood how sequenced activation patterns relate to differential muscle contraction, nor how segmental contraction creates the kinematics that drive the eyelid’s critical functions. In fact, motion of the eyelid has predominantly been modeled in only a single dimension (open–close). Here, we show that eyelid motion has important two-dimensional features that vary between eyelid behaviors. Using distributed intramuscular electromyography, we further show that activation differs segmentally across the OO, and that patterns of activation change to produce different behavior-specific eyelid kinematics. Our results demonstrate the role of segmental activation in eyelid motion, highlighting the importance of precise neural control in producing natural eyelid behavior. We anticipate that this research is a starting point for robust mechanistic models of eyelid function. This knowledge has critical implications for diagnosis and treatment of eyelid paralysis.